O bezpośredniej metodzie pomiaru prędkości powierzchni swobodnej ciała stałego - BYSZEWSKI, W.W.; DEMBIŃSKI, M.; MUCHA, Z. (Engineering Transactions, 1971)
A direct method op velocity measurement of a solid state free surface The subject of the paper is an optical method not hitherto propagated enabling direct observation of a free surface movement (or solid state as a whole). In this method, use is made of the camera for ultrarapid photography registering the motion of characteristic points of the surface investigated. The principal advantage of this method is its simplicity and fact that it enables instant velocity measurement. several points of the surface lying simultaneously on a selected straightline. This method is described using the example of an accelerated leaf in the plasma sector and the motion of a mylar leaf ejected during the explosion of the metal leaf. A comparison is made of this direct method with other known optical methods. Advantages and shortcomings are indicated.